Physical and spectroscopic properties of lithium-borosulfophosphate glasses doped with dysprosium and europium ions - Ibrahim Bulus, 1986-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains )) - Universiti Teknologi Malaysia, 2016